Federalism and Family - Adler, Libby (Columbia Journal of Gender and Law, 1999)
The Lopez decision reaffirms that family’s proper place under federalism is with the states. In the aftermath of Lopez, federal courts have been and will continue to be faced with controversies regarding which types of family matters may be accorded federal attention." This article seeks to shed some light on these controversies and aid reformers in advocating reforms that advance the interests of families under our federalist system. The article proceeds as follows: Part II introduces the rhetoric of federal incongruity with family and uses the issue of same-sex marriage to test the usefulness of this general rule. Part III identifies family-shaping rules in such wide-ranging areas of federal law as tax, bankruptcy, housing, and the whole gamut of benefits programs.’ This part also examines the history of early assistance programs designed to aid poor, female-headed families. During the 1920s and 30s, when these programs were being founded, progressive legal thinkers formulated a profoundly influential critique of the public/private distinction as it was used to justify laissez-faire treatment of the wage-labor market. While subverting this distinction for purposes of the wage-labor market, however, reformers of the period re-enacted the distinction on a new axis: the market/family axis. Part IV reviews the historical exclusion of family matters from federal court jurisdiction. It argues that the common law development of this exclusion reveals an ideological reliance on the public/private distinction along with a strategy of marshalling exceptions to preserve the rule of state governance of family. Part V jumps into the present to examine controversies surrounding two federal statutes, criminalizing failure to pay child support and acts of domestic violence, respectively. It argues that the rhetoric offered by supporters of these statutes further entrenches the ideology of the private, state-controlled family. Finally, part VI concludes that examples discussed throughout the article demonstrate the impossibility of confining family to the state sphere. As a result, proponents of the general rule against federal governance of family have been forced to deploy multiple exceptions-that is, to advocate federal governance of exceptional aspects of family, as a strategy for sustaining the rule.